2023
DOI: 10.3389/fphar.2023.971136
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-triggered Resolvin D1 ameliorates activation of the NLRP3 inflammasome via induction of autophagy in a rat model of neuropathic pain

Abstract: Background: Several studies performed thus far indicate that neuroinflammation may be one of the mechanisms underlying the pathogenesis of neuropathic pain (NP). Autophagy, as an adaptive response, has been regarded as an active process of removing the inflammatory stimulus and restoring homeostatic balance. Resolution of inflammation is a biochemical process mediated by the so-called aspirin-triggered specialized proresolving lipid mediators (AT-SPMs), which are thought to exert protective effects in NP. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is intriguing to speculate that autophagy maybe be playing an important role in HMC3 responses to poly(I:C) and induction of the inflammatory response. Recent data has shown that autophagy is involved in microglia induction of the important regulator of the Nod-like receptor protein 3 (NLRP3) inflammasome signaling pathway ( Wang et al, 2023b ), which is activated by a variety of TLR agonists including poly(I:C) and viruses. Autophagy alleviates sevoflurane-induced cognitive dysfunction in elderly rats ( Zhou et al, 2023 ) and autophagy is an important component of HIV-1 and drug-induced neuroinflammaging ( Sil et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing to speculate that autophagy maybe be playing an important role in HMC3 responses to poly(I:C) and induction of the inflammatory response. Recent data has shown that autophagy is involved in microglia induction of the important regulator of the Nod-like receptor protein 3 (NLRP3) inflammasome signaling pathway ( Wang et al, 2023b ), which is activated by a variety of TLR agonists including poly(I:C) and viruses. Autophagy alleviates sevoflurane-induced cognitive dysfunction in elderly rats ( Zhou et al, 2023 ) and autophagy is an important component of HIV-1 and drug-induced neuroinflammaging ( Sil et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection of RvE1 or AT-RvD1 attenuated mechanical and thermal hyperalgesia [106,107]. In addition, the activities of microglia and various types of pro-inflammatory cytokine expression, such as IL-1β, IL-18, and TNF-α, were reduced by AT-RvD1 [107].…”
Section: Spinal Nerve Ligation (Snl) Rat Modelmentioning
confidence: 96%
“…Additionally, unlike the inflammatory pain models, Rv studies using neuropathic pain models have confirmed changes in inflammatory factors and regulation of glial activation at the levels of the DRG and spinal cord (Table 2). Spinal cord [107] Rv treatment in neuropathic pain models alleviates pain responses such as mechanical and thermal hypersensitivity. Decreased inflammatory cytokines are confirmed at central and peripheral nerve system levels.…”
Section: Functions Of Resolvins In Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation